Towards a new classification of Muscidae (Diptera): a comparison of hypotheses based on multiple molecular phylogenetic approaches. (26th February 2021) - Grzywacz, Andrzej; Trzeciak, Paulina; Wiegmann, Brian M.; Cassel, Brian K.; Pape, Thomas; Walczak, Kinga; Bystrowski, Cezary; Nelson, Leanne; Piwczyński, Marcin
Abstract: Muscidae are a megadiverse dipteran family that exhibits extraordinary diversity in morphology and life history as both immatures and adults. The classification of Muscidae has been long debated, and most higher‐level relationships remain unknown. In this study, we used multilocus Sanger sequencing (mS‐seq), anchored hybrid enrichment (AHE) and restriction‐site associated DNA sequencing (RAD‐seq) approaches to examine relationships within Muscidae. The results from AHE and RAD‐seq largely correspond to those obtained from mS‐seq in terms of overall topology, yet phylogenomic approaches received much higher nodal support. The results from all molecular approaches contradict the traditional classification based predominantly on adult morphology, but provide an opportunity to re‐interpret the morphology of immature stages. Rearrangements in Muscidae classification are proposed as follows: (i) Mesembrina Meigen and Polietes Rondani are transferred from Muscinae to Azeliinae; (ii) Reinwardtiinae stat. rev. is resurrected as a subfamily distinct from Azeliinae; (iii) Eginia Robineau‐Desvoidy, Neohelina Malloch, Syngamoptera Schnabl and Xenotachina Malloch are transferred to Reinwardtiinae stat. rev. Abstract : We exploited for the first time a combination of multilocus Sanger sequencing (mS‐seq), anchored hybrid enrichment (AHE), and restriction site associated DNA sequencing (RAD‐seq) approaches to examine relationships within Muscidae. The results from AHE and RAD‐seq largely correspond to those obtained from mS‐seq in terms of overall topology, yet phylogenomic approaches received much higher nodal support. The results from all molecular approaches, while at odds with traditional classification based predominantly on adult morphology, are concordant with re‐interpreted immature stage morphology and natural history.